Earthquake hazards and mitigation. - Ayothiraman, R.; Hazarika, Hemanta (I.K. International Pub. House, 2008)
Contributed articles presented at the International Workshop on Earthquake Hazards and Mitigations on December 7 and 8, 2007 in Gauhati, India.